A review of major aspects of snook breeding (Revista de Ciências Agroveterinárias, 2013)
Marine fish breeding is an activity that presents great growth trend, in which one of the groups of fish with high commercial interest are the snooks of the genus Centropomus. Two species of this genus show favorable characteristics for captive breeding, the fat snook, C. parallelus, and common snook, C. undecimalis. This review has the objective of approaching the main aspects of snook breeding and their future prospects for the expansion of this activity. The technology for snook breeding is more advanced when compared to other marine species, however there are still some bottlenecks and further studies are necessary to obtain better performance levels in captivity, particularly during the fattening phase. The fat snook is the species with greater economic interest because it shows good adaptation to captive breeding and has more advanced breeding technology. Regarding the common snook, its reproduction has yet to be dominated.
Keywords: Centropomus; Fattening; Marine fish breeding; Reproduction.